The “Mortar Massacres”: A Controversy Revisited - Rusek, Benjamin; Ingrao, Charles (Nationalities papers, 2004)
One of the many controversies that survived the war in Bosnia-Herzegovina concerns the responsibility for several of the most deadly artillery attacks against civilians during the three-year siege of Sarajevo. Although indiscriminate artillery fire accounted for a small fraction of the total civilian deaths during the war, graphic video footage of the mass slaughter exercised a disproportionate effect on world public opinion and, therefore, on Western policymakers who felt constrained to “do something.” On at least three occasions, individual artillery explosions in the Bosnian capital prompted immediate international intervention that substantially determined the course and resolution of the conflict. The persistence of controversy is informed by a combination of factors, including the substantial consequences of the Western response, the inconclusiveness of some of the forensic data, and the conflicting statements of civilian survivors, journalists, spokesmen for the belligerents, and U.N. officials—all of whom have been accused of some degree of bias by one side or another. Nearly a decade later, testimony and forensic evidence presented at the International Criminal Tribunal for the Former Yugoslavia (ICTY) has shed new light on these incidents, presenting a more comprehensive and authoritative historical baseline account of the “mortar massacres,” much as it has for a plethora of criminal acts committed by all sides during the wars of Yugoslav succession. The Tribunal recently released documentation detailing some of the mortar attacks that occurred in the city of Sarajevo, including forensic reports compiled by the U.N. Protection Force (UNPROFOR) which had not been previously made public. The bulk of this information is contained in the Tribunal Judgment and corresponding Dissenting Opinion of the former commander of the Sarajevo Romanija Corps (SRK), Major General Stanislav Galić. Although the reliability of judicial testimony and other evidence is invariably limited by the abilities and resources of both the prosecution and defense, the trial transcript has cleared away at least some of the fog of war, making it somewhat less difficult to apportion responsibility for the disputed attacks. This article integrates the Galić transcript with earlier, wartime U.N. documentation, press releases, and media reports, supplemented by interviews conducted by the authors with military experts familiar with the characteristics of the weaponry employed by the besiegers. It also endeavors to place the most notorious incidents in the broader context presented by the multiplicity of artillery attacks that took place in urban areas across Bosnia between 1992 and 1995.